PENGEMBANGAN BUKU AJAR MATEMATIKA KELAS X SMA BERBASIS HOTS - Benny Hendriana; Rifdah Kurniawan; Ishaq Nuriadin (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The aim of this study is to develop mathematics textbooks based on High Order Thinking Skills (HOTS) for odd grade X students and improve the quality of teaching materials in terms of validity. This research is a development with Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The product of this research is HOTS-based mathematics textbooks. The results showed that this book has great quality based on several aspects, including valid or good criteria (score 70.70) as assessed by content experts; very valid or very good (score 95.14) as assessed by media experts; very valid or very good criteria (score 89.58) as assessed by linguists.